The Effect of Mindfulness-based Cognitive Behavior Therapy in Improving Self-Confidence of Broken Home Students - Rita Kartika Sari; Bagus Abdillah; Abdul Hadi; Faisal Faisal (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to determine the effectiveness of cognitive behaviour therapy with mindfulness techniques through group counselling to increase the confidence of high school students who experience a broken home, through experimental research with a single group pretest post-test design. The sample selection in the study was the purposive sampling technique, which obtained 8 samples from 12 populations that became the research sample. Data analysis used the Wilcoxon test to determine the increase in self-confidence before and after the intervention and the Mann Withney U Test to determine the differences between the intervention groups. The results of experiments that have been carried out show an increase in the self-confidence of students who experience a broken home after being given group counselling on cognitive behaviour therapy with mindfulness techniques.